A rare case of hypoplastic left heart syndrome in pregnancy and its outcome - Akshatha DS; Shakuntala PN; Sreelatha S; Sumayya; Shruthi (Barpeta Obstetrics and Gynaecological Society, 2022)
Hypoplastic left heart syndrome is abnormal development of left sided cardiac structure, leading to obstruction to blood flow from the left ventricular outflow tract. We are presenting a case of primigravida with 35weeks period of gestation with gestational hypertension with left hypoplastic heart syndrome with single umbilical artery which was diagnosed at 24weeks anomaly scan but she continued the pregnancy. Emergency caesarean section was done and a live male baby was delivered but shifted to NICU in view of antenatally diagnosed hypoplastic left heart syndrome. Baby was discharged on day 8 of life, on day 21 of life baby presented with gasping breaths. Chest x-ray showed extensive infiltrates and baby died due to pneumonia and cardiac arrest.